PENGARUH STRATEGI PEMBELAJARAN INKUIRI TERHADAP KEMAMPUAN SAINS ANAK KELOMPOK B DI RA DARUL FAZRI DESA LAUT DENDANG T.A 2018/2019 - Salpina Simahate (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2019)
This study aims to find: (1) Children's Science Ability (2) Science Ability Children use inquiry learning strategies (3) Significant influence of inquiry learning strategies on children's scientific abilities in RA. Darul Fazri T.A. 2018/2019. The type of research conducted is experimental research with a quantitative approach. The results showed that Inquiry learning strategies influenced the scientific ability of group B children. This was base on the results of the research in the experimental class, obtained results of children's scientific abilities with an average score of pre-test 4 and post-test 9 average scores with scores the highest post-test 12 and the lowest value 4 so that the scientific ability of children in the experimental class is better than the control class. The scientific abilities of children in the control class get an average score of 4.3 tests and an average post-test of 5.8 with the highest score of 10 and the lowest value of 4. This is also based on the results of hypothesis testing, namely tcount> t table and the results obtained testing is 4.38>2.047 with a significant number of α = 0.05. Thus the hypothesis Ho is rejecting and Ha is accept so that it can being stated that there is a significant effect of Inquiry Learning Strategy on the Science Ability of Group B Children Aged 5-6